Compact X‐band CMOS bidirectional gain amplifier without T/R switches. Issue 1 (1st January 2013) - Cho, Moon‐Kyu; Baek, Donghyun; Kim, Jeong‐Geun
Abstract : Presented is a compact X‐band bidirectional gain amplifier in 0.18 μ m CMOS, which eliminates two T/R switches in the conventional one. The gain of >14 dB and the in/output return losses of >8 dB are achieved at 8–14 GHz. The measured output P1dB is ~1 dBm at 10 GHz. The chip size is 0.62 × 0.60 mm 2, which is compact due to the removal of two T/R switches for the bidirectional operation. The DC power consumption is 54 mW at 1.8 V supply voltage. Nearly identical performance is achieved in the forward and reverse operations at X‐band. To the authors' knowledge, this is the first demonstration of an X‐band CMOS bidirectional gain amplifier with the smallest size.